Minority Party Government and Independent MPs: A Comparative Analysis of Australia and Ireland. Issue 1 (23rd October 2018) - Kefford, Glenn; Weeks, Liam
Abstract: Minority government is becoming more common. With support declining for traditional parties and increasing for anti-establishment movements, government formation is becoming increasingly difficult in many jurisdictions. While minority government has been the subject of much normative debate, one type of minority arrangement that has not attracted much attention is that involving independent parliamentarians. Government in most countries tends to be party government, but in this article, we examine the experience in Australia and Ireland of independents supporting minority government. We assess the performance of these administrations in terms of their stability, their productivity and their electoral performance. We find that, contrary to expectation, minority government involving independents is not a recipe for instability nor necessarily results in an efficient parliament.